2021
DOI: 10.1002/fft2.79
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides isolated from Laminaria japonica attenuates gestational diabetes mellitus by regulating the gut microbiota in mice

Abstract: The current study was aimed to explore the beneficial effects of polysaccharides isolated from Laminaria japonica (LP) on gestational diabetes mellitus (GDM) mice. The obtained results demonstrated that the LP improved serum biochemical index, body weight index, and glucose tolerance. Furthermore, the evidence also suggested that the beneficial effects of LP might be attributed to the alternation in gut microbiota by LP supplementation. Particularly, the Turicibacter, a short‐chain fatty acids‐producing bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 30 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…After glucose administration, the high level of fasting blood glucose was detected in CPPL. This was owing to the fact that CPPL is insufficient to effectively control postprandial blood glucose at normal levels, or lead to nocturnal hypoglycemia and then lead to increase in hyperglycemic hormones in the morning ( Bolli et al, 1984 , Lin et al, 2021 ). Blood glucose peaked at 30 min in the AD group, reaching 30.6 ± 5.4 mmol/L, and then decreased to 29.72 ± 2.50 mmol/L at 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…After glucose administration, the high level of fasting blood glucose was detected in CPPL. This was owing to the fact that CPPL is insufficient to effectively control postprandial blood glucose at normal levels, or lead to nocturnal hypoglycemia and then lead to increase in hyperglycemic hormones in the morning ( Bolli et al, 1984 , Lin et al, 2021 ). Blood glucose peaked at 30 min in the AD group, reaching 30.6 ± 5.4 mmol/L, and then decreased to 29.72 ± 2.50 mmol/L at 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…The gut microbiota plays a crucial role in maintaining metabolic health ( Lin et al, 2021b ; Shanmugam et al, 2022 ). The current study showed that ULO has the capacity to regulate gut microbiota structure under ageing-related diabetes conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the relationships between the fermentation properties of dietary fibers and their structural characteristics have attracted increasing attention (Bang et al, 2018; Beukema et al, 2020; Blanco‐Pérez et al, 2021; Ferreira et al, 2018; Lin et al, 2021; Y. Zhang et al, 2021). In vitro anaerobic fermentation that mimics the mammalian colon has been regarded as a useful tool to support studies of diet–gut microbiota interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation with the three kinds of pectin induced slightly higher content of propionic acid than glucose and the blank control (Figure 7B), and no significant alterations were observed in isovaleric acid within different groups (Figure 7E). In recent years, the relationships between the fermentation properties of dietary fibers and their structural characteristics have attracted increasing attention (Bang et al, 2018;Beukema et al, 2020;Blanco-Pérez et al, 2021;Ferreira et al, 2018;Lin et al, 2021;. In vitro anaerobic fermentation that mimics the mammalian colon has been regarded as a useful tool to support studies of diet-gut microbiota interactions.…”
Section: Pectin With Various Degrees Of Esterification Influenced Scf...mentioning
confidence: 99%